Intelligent Mobile Projects with TensorFlow: Build 10+ Artificial Intelligence Apps Using TensorFlow Mobile and Lite for IOS, Android, and Raspberry Pi - Tang, Jeff (Packt Publishing, Limited, 2018)
Google TensorFlow is used to train all the models deployed and running on mobile devices. This book covers 10 projects on the implementation of all major AI areas on iOS, Android, and Raspberry Pi: computer vision, speech and language processing, and machine learning, including traditional, reinforcement, and deep reinforcement.